(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article based on the «viable measure» of Kazakh literary language and to explore it’s re-direction form of the study. In linguistic’s «the viably» used with the concept of vitalistic. On the one hand, it’s cause of category will be as a living-phenomenon, in the other hand, all the language genres are based on it’s active functioning. Thus, Kazakh literary language’s «viably» feature will be review in the new research side of Kazakh linguistic study.